(untitled) (European Journal of Teaching and Education, 2020)
The fundamental research question from which this paper is going to be - is there an alternative to alternative education? Alternative schools are in the pedagogical and didactical understanding of teaching, often far ahead of their time, sometimes too far. They offer something new and different, much better than traditional classes. Starting from the central location of students in the curriculum, up to curriculum development and teaching classroom design, this school offers us another option - an alternative. This paper represents selected alternative schools and the answer to the research question, and it is in differentiation. Differentiated school is the third alternative and the side by side with alternative schools brings something new and special. The methodology derives from the twenty-day observation of the teaching and the overall work of the gender-differentiated school with teacher interviews. In this qualitative research, the work of the male school that works on the principle of gender differentiation was analyzed and the specialties that this school achieved are described. The most important of them is the principle of work in a homogenous environment and a mentoring system that reinforces the underlying idea of better education. The specialties of gender differentiation are presented and its place in other possibilities of differentiation. The whole work presents a comparative analysis of alternative schools and differentiation and a conclusion about the greater success of such models compared to traditional schools.